Activity system for intercultural competence development at the Facultad de Ciencias Médicas “Enrique Cabrera”, La Habana - Yunet Tahimí Hernández-Vázquez; Yamila Vázquez-Pérez; Yohandra Valdés-Roque; Yohalis Valdés-Roque; Rafael Saúl González-Ponce de León (Revista Información Científica, 2023)
Introduction: language influences the way of thinking, living and the relationships of speakers because its role for reflecting the realities of each human group and the transmission of knowledge. This means that the communication and learning of English as foreign language includes elements present in the language culture.